PENGARUH BELANJA MODAL DAN PERTUMBUHAN EKONOMI TERHADAP TINGKAT KEMISKINAN DI PROVINSI SE KALIMANTAN PERIODE 2001-2013 - B01111014, Murkan (Jurnal Pembangunan dan Pemerataan, 2016)
Economic increase will have an impact on capital expenditures and economic growth and results in reducing the level of poverty. In this condition, the government should help people increase their welfare and reduce the poverty.This study discussed “The Effect of Capital Expenditure and Economic Growth on Poverty Level in the Province of Kalimantan from 2001 to 2013". This study focused on the issue of whether capital spending and economic growth significantly influenced the level of poverty in the province of Kalimantan from 2001-2013.The type of research was quantitative descriptive research that aimed to determine number of influences of capital spending and economic growth on poverty level in the province of Kalimantan from 2001 to 2013. In collecting the data, researcher used secondary data obtained from the Central Statistics Agency (BPS) of West Kalimantan province by using panel data time series and cross section. The collected data was analyzed by using Eviews 8.0 calculation.The research findings showed that in partial capital expenditure (X1) and economic growth (X2) had a significant influence on the level of poverty in the province of Kalimantan from 2001 to 2013 with probability (0.0300) and (0.0139) smaller than α = 5%. While simultaneously both variable capital spending and economic growth affected the level of poverty in Kalimantan provinces between 2001and 2013 with F-statistic value more than 4.562048 F table or more than 3,19 F table with the probability of the value of 0 , 015 243 smaller than α = 5%.It is suggested that the local government should prioritize an increase in capital expenditures compared to other expenditures and plan development programs efficiently. To reduce the level of poverty in the provinces of Kalimantan, the economic development needs to be increased. In addition, the infrastructures such as roads, bridges, piers, water, electricity, education, health, housing, and hospitals should support the programs, as a result the poverty in the region of Kalimantan can be reduced.Keywords: Capital Expenditures, Economic Growth and Poverty.